A Case Report of Speech Arrest Following Meningioma Resection in Elderly Patients - Bedarkar, Shivani; Jha, Deepak; Akbar, Md.; Kolekar, Vedant; Kawre, Tejas; Jain, Ashish (Indian Journal of Pharmacy Practice)
Meningiomas, benign tumors arising from the meninges, present unique challenges in treatment due to their varied clinical behaviors and potential for complications. This case report documents the surgical management and early postoperative complications in a 75-year-old male patient with a large meningioma affecting speech production due to its proximity to Broca's area. Despite meticulous surgical technique and postoperative care, the patient experienced prolonged speech arrest, which persisted beyond initial expectations. This case emphasizes the complexities in managing meningiomas, especially in elderly patients with comorbidities, and highlights the critical considerations in surgical decision-making and postoperative monitoring.
Keywords: Meningioma; Surgical resection; Elderly patients; Speech arrest; Complications; Postoperative care